X-ray spectral diagnostics of laser harmonic generation in the interaction of relativistic femtosecond laser pulses with clusters. (April 2016) - Faenov, A.Ya.; Oks, E.; Dalimier, E.; Skobelev, I.Yu.; Pikuz, S.A.; Pikuz, T.A.; Zhvaniya, I.A.; Fukuda, Y.; Andreev, A.; Koga, J.; Sakaki, H.; Kotaki, H.; et al.
Abstract: It is shown that the production of X-ray emission spectra in the interaction of high-intensity laser radiation with cluster targets may be affected by the bichromatic oscillating electric field arising from the generation of the second harmonic of laser radiation. A technique is proposed for diagnosing harmonic generation in laser – cluster interactions using the spectral line profiles of multiply charged helium ions. The efficiency of second harmonic generation at a laser intensity of is shown to amount to about 2 %.